2014
DOI: 10.1097/cad.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of tuftsin-derived T peptide in postoperative residual tumors

Abstract: Immune adjuvants have been used in cancer biotherapies to stimulate immune response to tumor cells. Despite their potential as anticancer reagents, there are several impediments to their use in clinical applications. In this study, we aim to modify the existing tuftsin structure and evaluate its antitumor activity in preclinical models. We synthesized a novel tuftsin derivative, namely, the T peptide (TP), by linking four tuftsin peptides, which showed enhanced stability in vivo. We then evaluated its anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the second set of surgical trials after the transplantation of live tumor cells and the appearance of solid tumor formations as mentioned in Animal Tumor Model , a surgical extirpation of the tumor formation was carried out (Toshkova and others ) when the average tumor volume reached about 300 to 350 mm 3 . The volume of remaining tumor was approximately 40 to 100 mm 3 after anesthetization by intravenous injection with 0.5% sodium pentobarbital solution (An and others ). The animal model described above simulated that incomplete resection resulted in residual existing in the tumor focus after surgical removal of tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…In the second set of surgical trials after the transplantation of live tumor cells and the appearance of solid tumor formations as mentioned in Animal Tumor Model , a surgical extirpation of the tumor formation was carried out (Toshkova and others ) when the average tumor volume reached about 300 to 350 mm 3 . The volume of remaining tumor was approximately 40 to 100 mm 3 after anesthetization by intravenous injection with 0.5% sodium pentobarbital solution (An and others ). The animal model described above simulated that incomplete resection resulted in residual existing in the tumor focus after surgical removal of tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were housed in a controlled environment at 23 ± 2°C under a 12 h dark/light cycle with free access to irradiated food and sterile water. We established a murine model with a postsurgical residual tumour to mimic the recurrence of solid tumour as described previously (An et al, 2014). The LOVO tumour cells (over 5 × 10 7 mL À1 ) were harvested and washed with sodium chloride.…”
Section: Postsurgical Residual Tumour Xenograft Models and Antitumour Effect Assaymentioning
confidence: 99%
“…The elementary structure of tuftsin-derived T-peptide is (Thr-Lys-Pro-Arg-AAN)4-(Lys-AAN)2-Lys-AAN, which has been granted a patent in China (CN-101007842A). Recently, it had been demonstrated that tuftsin-derived T-peptide was a potential postoperative adjuvant in cancer therapy, and it showed an inhibitory effect on growth of residual tumor cells after surgical resection 42 . In the current study, the objective was to investigate the effect of tuftsin-derived T-peptide on cell-mediated immunity after LPS stimulation and the survival rate in septic mice.…”
mentioning
confidence: 99%